Пам’яткоохоронна діяльність у Чернігові у 1919-1920-х рр.: шляхи реалізації - Непотенко, І. (Сiверянський лiтопис, 2016)
У статті розкрито способи впровадження пам’яткоохоронної діяльності в умовах становлення радянської влади, а також розглянуто проблеми, пов’язані з їхньою реалізацією. В статье раскрыто способы охранной деятельности памятников старины в условиях становления советской власти, а также рассмотрено проблемы, касательно их реализации. During the hostilities of 1918-1919 Chernihiv was damaged substantially. Most of the
housing stock was also destroyed. Among the buildings there were some buildings with historical
and cultural value and were the best examples of external facades or internal decoration.
According to the Decree of the Council of People’s Commissars of April 3rd, 1919 all premises
with historical and cultural significance have been transferred to the People’s Commissariat
of Education. Since February 1919 the section of folk graphic art took care about the
monuments of the old everyday life and art. March 21, 1919 a special section was separated
– the Committee for the protection of monuments of art and antiquities. The Committee was
obliged to take care of the protection, exploration and popularization of the monuments.
Initially, the Committee consisted of the chairman (Yu. Vynohradkyi), two members and a
few emissaries. After a year their number increased to eight. The Staff of the Committee
took care of archives and museums. They examined the town churches. In particular, in 1919
four of them were examined. Moreover, the Committee took part in the property requisition
in order to save them from its destruction. Most of the confiscated things were transferred to
the newly established museum. Consequently, the Committee activity was substantive and diverse. Despite the unfavorable conditions, the activity, in conditions of the new Soviet government, financial difficulties and
the civil war, continued to work. It enabled to save a lot of historical and art things.